Front crawl swimming analysis using accelerometers: a preliminary comparison between pool and flume - Espinosa, H. G.; Nordsborg, N.; Thiel, D. V. (Procedia Engineering, 2015)
Biomechanical characteristics such as stroke rate and stroke length can be used to determine the velocity of a swimmer and can be analysed in both a swimming pool and a flume. The aim of the present preliminary study was to investigate the differences between the acceleration data collected from a swimming pool with that collected from a flume, as a function of the swimmer's stroke rate and stroke count, with the objective of identifying the impact on the swimmer's performance. The differences were determined by the analysis of the stroke's features, comparing several strokes normalized to one stroke count from an elite swimmer. Triaxial accelerometer logging using a sensor located in an arm band positioned immediately in the wrist was used to record the swimmer's stroke. There is statistical evidence that show that there are small differences between the pool and flume on medio-lateral wrist movements (0.64 </= r </= 0.75). The correlation coefficients are (0.75 </= r </= 0.83) and (0.82 </= r </= 0.89) for the other two axes.